P-075 YI Use of Standardized Quality Measure (QM) Worksheet, Improves Documentation of Quality and Results in Improved Quality Care for IBD Patients. (March 2016) - Siddiki, Hassan; Howard, Bridget; Khalid, Mohammad; Noelting, Jessica; Leighton, Jonathan; Pasha, Shabana; Heigh, Russell; Gurudu, Suryakanth
Abstract : Background: IBD is a chronic illness that can have a variable course of disease progression. Studies show up to 11% IBD patients receive care that not recommended in guidelines and is potentially harmful. Hence there is need to improve quality by standardizing care, that can be quantified. AGA/CCFA has endorsed a set of IBD-specific process-measures that are currently incorporated into the Physician Quality Reporting System (PQRS). In the year 2012 to 2013, our IBD group adopted a standardized worksheet based on 10 highest yielding QMs recommended by AGA/CCFA (sample worksheet Figure1). This worksheet was available in electronic medical system (EMR) and was filled annually by our nurse practitioner from responses obtained on routine follow-up patient visit. This worksheet itemized applicable quality indicators and allowed us the opportunity to quantify not only improvement in documentation of QMs but also improved clinical outcomes. Our aims were (1) An electronic health maintenance worksheet improves documentation of quality indicators; (2) The worksheet improves quality care in IBD patients. Methods: All consecutive patients with established IBD, who had a health maintenance worksheet filled during return visits in the year 2012 and 2013 were included. To measure improvement in documentation of quality indicators, clinical notes from 12 months prior to filling of the worksheet were reviewed and all quality indicators mentioned in any of those notes were recorded. Patients who did not have an encounter with a health care provider in 12 months prior, were excluded. Patients who had a new diagnosis of IBD were also excluded. To measure if completion of worksheet actually translated to better care and not just improved documentation, we recorded every time a medical intervention was performed, when any QM was identified lacking on the worksheet. Statistical analysis was done using means and standards deviations (SD). Pre and post intervention data was analyzed using paired t-test with alpha level 0.05. Results: Ninety-five patients were identified with mean age of 47 years (SD 17) and 63% were men. 65% had CD and 35% UC with a mean length of disease of 12 years (Range 1–25 years). Mean QM indicators recorded in 12 months prior to filling the worksheet were 2 per patient (SD 1.4). Mean QM indicators identified for the same cohort of patients after completing worksheet was 5.8 (SD 1.22). For each patient the paired data of pre and post intervention showed mean improvement in recorded quality indicators was 3.9 items per patient (SD 0.16), which was statistically significant, P -value <0.001 (Figure 2). A deficiency identified by the worksheet resulted in medical intervention in 76% of patients (N = 73). In 10% of patients, 3 or more interventions were done. Common interventions included orders for bone density scans, vaccinations, colonoscopy for dysplasia surveillance and dermatology referral for skin exam for patients on immune suppression. Conclusions: A standardized QM worksheet when incorporated into clinical practice as a part of EMR, improved documentation of quality measures and resulted in improved quality care for patients with known IBD.